Early effect modeling of silicon-on-insulator SiGe heterojunction bipolar transistors - 徐小波 张鹤鸣 胡辉勇 马建立 (Chinese physics B, 2011)
Silicon germanium （SiGe） heterojunction bipolar transistor （HBT） on thin silicon-on-insulator （SOI） has recently been demonstrated and integrated into the latest SOI BiCMOS technology. The Early effect of the SOI SiGe HBT is analysed considering vertical and horizontal collector depletion, which is different from that of a bulk counterpart. A new compact formula of the Early voltage is presented and validated by an ISE TCAD simulation. The Early voltage shows a kink with the increase of the reverse base-collector bias. Large differences are observed between SOI devices and their bulk counterparts. The presented Early effect model can be employed for a fast evaluation of the Early voltage and is useful to the design, the simulation and the fabrication of high performance SOI SiCe devices and circuits.